Sub-chronic variable stress induces sex-specific effects on glutamatergic synapses in the nucleus accumbens. (14th May 2017) - Brancato, Anna; Bregman, Dana; Ahn, H. Francisica; Pfau, Madeline L.; Menard, Caroline; Cannizzaro, Carla; Russo, Scott J.; Hodes, Georgia E.
Highlights: 6 days of variable stress sex specifically decreases VGLUT1 in NAc. Variable stress increases VGLUT2 in NAc threefold higher in females than males. Variable stress does not alter spine density or morphology in either sex. Variable stress does not alter expression of PSD-95 or TH in either sex. Stressed females undergo circuit-specific activation of glutamatergic synapses. Abstract: Men and women manifest different symptoms of depression and under current diagnostic criteria, depression is twice as prevalent in woman. However, little is known of the mechanisms contributing to these important sex differences. Sub-chronic variable stress (SCVS), a rodent model of depression, induces depression-like behaviors in female mice only, modeling clinical evidence of higher susceptibility to mood disorders in women. Accumulating evidence indicates that altered neuroplasticity of excitatory synapses in the nucleus accumbens (NAc) is a key pathophysiological feature of susceptibility to social stress in males. Here we investigated the effects of SCVS on pre- and post-synaptic protein levels and morphology of glutamatergic synapses of medium spiny neurons (MSNs) in the NAc of female and male mice. Animals underwent six-day exposure to alternating stressors including shock, tail suspension and restraint. MSNs from the NAc were filled with a Lucifer yellow dye and spine density and type were examined using NeuronStudio. In a separate group of animals, immunofluorescence staining was performed for vesicular glutamate transporter 1 (VGLUT1) and vesicular glutamate transporter 2 (VGLUT2), in order to label cortical and subcortical glutamatergic terminals. Immunostaining for post-synaptic density 95 (PSD95) was employed to evaluate post-synaptic density. Females demonstrated circuit-specific pre-synaptic alterations in VGLUT1 and VGLUT2 containing synapses that may contribute to stress susceptibility in the absence of post-synaptic alterations in PSD95 puncta, spine density or type. These data indicate that susceptibility to stress in females is associated with changes in the frequency of distinct glutamatergic inputs to the NAc.